Renewable energy systems from biomass : efficiency, innovation and sustainability - Strezov, Vladimir; Anawar, Hossain M. (CRC press, 2019)
"A fast-growing interest in the realm of renewable energy, the authors here have identified a need to synthesize relevant and up-to-date information in a single volume. They describe a systems approach to renewable energy and discuss technological, political, economic, social and environmental viewpoints, as well as policies and benefits"--